2022
DOI: 10.3390/livers3010001
|View full text |Cite
|
Sign up to set email alerts
|

Support Needs and Coping Strategies in Non-Alcoholic Fatty Liver Disease (NAFLD): A Multidisciplinary Approach to Potential Unmet Challenges beyond Pharmacological Treatment

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most frequently occurring chronic liver disease, affecting approximately 25–30% of the adult general population worldwide. NAFLD reflects excess hepatic accumulation of fat in the absence of increased alcohol intake, and, due to its close association with obesity, is frequently referred to as the ‘hepatic manifestation’ of metabolic syndrome. Indeed, a high percentage of individuals with NAFLD present with a combination of the cardio-metabolic comorbidities that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…It is important to highlight that there could be many other factors that may contribute to the mental health and well-being of patients with NAFLD, including symptoms of fatigue which may impact on quality of life and the high risk of significant complications, as well as the lack of awareness of the condition and perceived stigmatization ( 28 ). Furthermore, it is reported that NAFLD patients with depression are at a greater risk of adverse outcomes, such as stroke, CVD and cancer-related mortality compared to those without depression ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to highlight that there could be many other factors that may contribute to the mental health and well-being of patients with NAFLD, including symptoms of fatigue which may impact on quality of life and the high risk of significant complications, as well as the lack of awareness of the condition and perceived stigmatization ( 28 ). Furthermore, it is reported that NAFLD patients with depression are at a greater risk of adverse outcomes, such as stroke, CVD and cancer-related mortality compared to those without depression ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, NAFLD is a complex condition and may further be associated with various socioeconomic factors and unmet needs, which could in turn lead to mood imbalances and feelings of social isolation and loneliness, representing a further substantial risk to overall health and quality of life ( 28 ). Interestingly, chronic loneliness is reported as being associated with both mental health problems and metabolic disorders, potentially acting as a chronic stressor leading to HPA axis overactivity which may contribute to the development of both mental health and metabolic problems that, in turn, may also lead to feelings of social isolation ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The panel felt strongly about the need to study the impact of treatment and care on overall quality of life, including functional status (priority 5.2; ranked 1st in its domain). Knowledge gaps remain about patient needs and experiences, 88 including perspectives around prevention, treatment, and care. The panel prioritised studies that can advance this understanding (priority 5.1; ranked 2nd in its domain).…”
Section: Patient and Community Perspectivesmentioning
confidence: 99%
“…Mental health issues are a common problem facing CLD patients, and a cause for isolation and withdrawal in health-seeking [15]. The nancial burden for CLD patients is known to be associated with anxiety and depression [16], as well as worry and fatigue [17].…”
mentioning
confidence: 99%